2020
DOI: 10.31014/aior.1994.03.02.114
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Service Quality, a Key to Improved Patient Satisfaction and Loyalty in Healthcare Delivery: The Servqual Dimension Approach

Abstract: The Journal of Health and Medical Sciences is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…5 According to the report by Bentum-Micah et al, some non-specialized factors, such as assurance and empathy, can affect patient loyalty. 8 "Skill and expertise" is a highly scored determinant. Appropriate behavior builds physician-patient trust, which has been shown to improve patient adherence and compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 According to the report by Bentum-Micah et al, some non-specialized factors, such as assurance and empathy, can affect patient loyalty. 8 "Skill and expertise" is a highly scored determinant. Appropriate behavior builds physician-patient trust, which has been shown to improve patient adherence and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…3 Loyal patients will likely return to the same providers, distribute the positive word of mouth, and finally recommend the physician to friends and acquaintances. 4 Many factors are influential in the loyalty of patients to the doctor, such as reliability quality, 5 doctors' interaction behavior, 6 service quality, 7 empathy, 8 nursing care 9 and patient satisfaction. 10 Medical personnel's behavior, physicians' emotional behavior, and nurses' behavior are correlated with patient loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…"The study incited that patients' satisfaction and loyalty are influenced by the quality of medical/hospital services through its five components: reliability, assurance, tangibility, empathy and responsiveness" [Bentum-Micah et al, 2020] ii.…”
Section: Repurchase Intention Of Patientsmentioning
confidence: 99%
“…Kondasani and Panda [54] found that the quality of amenities (tangible dimension) positively impacts patients' loyalty and satisfaction. Service quality dimensions (responsiveness, empathy and assurance) impact patient loyalty, while tangibility and reliability have not any influence on loyalty [55]. The doctor's expertise encourages patients to repurchase the same service, which increases customer retention [56].…”
Section: Relationship Between Service Quality Patient Satisfaction An...mentioning
confidence: 99%